The Implementation of Vlan Segmentation and Access Control List Security at PT. Justus Kimiaraya - Taufik Rahman; Aditia Firdaus Saputra (EDUTIC, 2026)
In a corporate environment with various divisions and high data exchange activity, efficient and secure network management becomes crucial. PT. Justus Kimiaraya, as a distribution and production company, requires a network system capable of supporting inter-division data communication without compromising performance or security. This research aims to implement Virtual Local Area Network (VLAN) technology to enhance network segmentation and restrict inter-division access according to operational needs. The methods used include literature studies, analysis of existing network requirements, VLAN topology design using Cisco Packet Tracer, implementation of VLAN and Access Control List (ACL), and performance testing before and after implementation. The test results show that VLANs successfully separate data traffic between divisions, preventing interference. Additionally, ACLs implemented on the router effectively limit inter-VLAN access, especially for divisions not authorized to access certain services, such as switchs or other division networks.